Cognitive training and mild cognitive impairment : a review - Chua, Xavier Cheng En (Nanyang Technological University, 2020)
Mild cognitive impairment (MCI) is largely viewed as a pre-clinical stage in the trajectory of Alzheimer’s disease (AD) where the extent of cognitive decline is relatively mild, thus allowing for the application of earlier, more effective treatment. Cognitive training (CT), a form of cognitive intervention, can be subdivided into memory strategy training and cognitive exercise. While CT has shown promise in its ability to temporarily restore cognitive function and stimulate neuroplasticity in the MCI individual, early research in this area often suffered from poor methodological quality. This review evaluates the efficacy of CT in MCI based on the present research available. Additionally, results from the application of functional magnetic resonance imaging (fMRI) and other neurobiological measures provide evidence for CT-induced neuroplasticity in the MCI individual. However, such findings have yet to be explored cohesively from a theoretical standpoint. This review uses the theory of brain/cognitive reserve (Stern et al., 2018) as a basis for discussing these findings. At the conclusion, this review finds that the present research provides better support for the effectiveness of CT in MCI. For memory strategy training, a multidomain treatment approach appears to be more effective in generating positive results, while in cognitive exercise, more focused and individualised treatments tend to fair better. While present research lacks consensus on predictors of efficacy, this review finds the largely positive results of current studies promising, nonetheless. Potential future directions for research are discussed as well. Keywords: Cognitive Training, Memory Strategy Training, Cognitive Exercises, Mild Cognitive Impairment